已知列表x = [1, 2],那么执行语句 x.extend([3])之后,x的值为[1, 2, 3]
A: 正确
B: 错误
A: 正确
B: 错误
举一反三
- 已知列表 x = [1, 2],那么执行语句 x.extend([3]) 之后, x的值为____________如果:已知列表 x = [1, 2],那么执行语句 x.append([3]) 之后,x的值为_____________
- 已知列表x = [1, 2],那么执行语句x.extend([3]) 之后, x的值为___()_______。 A: [[1], [2]] B: [1, 2, 3] C: [3, 1, 2] D: [1, 2, [3]]
- 已知列表 x = ['1', '2'],那么执行语句 x.append(['3']) 之后,x 的值为 ( ) A: ['1', '2', '3'] B: ['1', ''2, ['3']] C: ['1'] D: ['3']
- 已知列表 x = [1, 2,3],那么执行语句 x.append([3]) 之后,x的值为_____________。 A: [1, 2,3,[3]] B: [1, 2,3,3] C: [1, 2,[3]] D: 1,2,3,[3]
- 已知列表x = [1, 2],那么执行语句x.extend(3)之后,x的值为 。